Tumor-Specific Blood Serum Factors as Basis of Tumor Dormancy - Donenko, Fedor V.; Kormosh, Natalia G.; Efferth, Thomas; Kiselevski, Michail V. (International Journal of Biotechnology for Wellness Industries, 2014)
In the present review, we focus on the importance of blood serum factors for tumor growth in vivo. Data from mice experiments indicate the existence of serum factors, which decrease the dormancy of Ehrlich carcinoma cells from 85 to 20%. The impaired production of these factors increases the life span of tumor-bearing animals from 14 days to 120 days. Blocking the production of tumor-specific factors causes the complete regression of already developed Ehrlich carcinoma. These serum factors do not affect the malignant carcinoma cells in vitro. We identified serpins as tumor dormancy serum factors. Experimental evidence suggests that serpins are not only essential for tumor growth. Serpins are also involved in the regeneration of normal tissues, such as adipose tissue, recurrence after cosmetic operations (liposuction), inhibiting rejection after liver transplantation, protection of parasitic flat worms living in host tissues and organs etc. We conclude that the inhibition of serum dormancy factor may represent attractive novel strategies for the prevention and treatment of relapsed cancers.